Pelatihan Eksplorasi Mocktail Dengan Sentuhan Rempah Nusantara Bagi Kampung Adat Cireundeu Bandung - Gilang Fahreza; Lilik Edi Saputro (BADAN PENERBIT STIEPARI PRESS, 2024)
Cireundeu Traditional Village is in Leuwigajah Village, South Cimahi District and has a population of 800 people. Most of the people in the Cireundeu Traditional Village work as cassava farmers and adhere to the Sundanese Wiwitan belief. The traditional potential must be supported by development, especially in the field of providing food and drinks that utilize village potential. Spices are a strong potential of the Cirendeu Traditional Village, they can come from various parts of plants, such as flowers, fruit, bark, stems, tubers, leaves and rhizomes. Spices can not only be used as seasonings for cooking, but can also provide taste, aroma and health benefits to various drinks. The Faculty of Economics and Business, Bina Sarana Informatics University Hospitality Study Program will hold community service with the theme